ERG system for neurotoxicity risk assessment - Tkachuk, Roman; Yavorskyy, Bohdan (Видавництво Львівської політехніки, 2010)
In this thesis the conceptual background for development of a neurotoxicity risk assessment electroretinographical system are given.
Keywords: neurotoxicity; assessment; electroretino - signal; adaptive signal processing; Kalman filter; system effectivity